Using Activated Carbon developed from Iraqi Date Palm Seeds as Permeable Reactive Barrier for Remediation of Groundwater Contaminated with Copper - Abd Ali, Ziad T. (Al-Khwarizmi Engineering Journal, 2017)
The possibility of using activated carbon developed from date palm seeds wastes as a permeable reactive barrier (PRB) to remove copper from polluted shallow groundwater was investigated. The activated carbon has been developed from date palm seeds by dehydrating methods using concentrated sulfuric acid. Batch tests were performed to characterize the equilibrium sorption properties of new activated carbon in copper-containing aqueous solutions, while the sandy soil (aquifer) was assumed to be inert. Under the studied conditions, the Langmuir isotherm model gives a better fit for the sorption data of copper by activated carbon than other models. At a pilot scale, One-dimensional column experiments were performed, and an integrated model based on the solution of an advection-reaction-dispersion mass balance equation, using COMSOL Multiphysics 3.5a software which is based on finite element method, was developed to study the space and time concentration of copper within groundwater. Experimental and numerical results proved that the PRB represents a potential role in the restriction of the copper plume migration. Also, these results showed that the greater thickness of PRB results in a better treatment of copper and that the barrier starts to saturate with contaminant as a function of the travel time. However, a good agreement between the predicted (theoretical) and experimental results with RMSE not exceeded the 0.08 proved these methods are effective and efficient tools in description of copper transport phenomena adopted here.